Relative effectiveness of robot‐assisted and standard laparoscopic prostatectomy as alternatives to open radical prostatectomy for treatment of localised prostate cancer: a systematic review and mixed treatment comparison meta‐analysis. (26th July 2013) - Robertson, Clare; Close, Andrew; Fraser, Cynthia; Gurung, Tara; Jia, Xueli; Sharma, Pawana; Vale, Luke; Ramsay, Craig; Pickard, Robert
Abstract : Objective: To compare the effectiveness of robot‐assisted and standard laparoscopic prostatectomy. Methods: A care pathway was described. We performed a systematic literature review based on a search of Medline, Medline in Process, Embase, Biosis, Science Citation Index, Cochrane Controlled Trials Register, Current Controlled Trials, Clinical Trials, WHO International Clinical Trials Registry and NIH Reporter, the Health Technology Assessment databases, the Database of Abstracts of Reviews of Effects, and relevant conference abstracts up to 31st October 2010). Additionally, reference lists were scanned, an expert panel consulted, and websites of manufacturers, professional organisations, and regulatory bodies were checked. We selected randomised controlled trials (RCTs) and non‐randomised comparative studies, published after 1st January 1995, including men with localised prostate cancer undergoing robot‐assisted or laparoscopic prostatectomy compared with the other procedure or with open prostatectomy. Studies where at least 90% of included men had clinical tumour stages T1 to T2 and which reported at least one of our specified outcomes were eligible for inclusion. A mixed‐treatment comparison meta‐analysis was performed to generate comparative statistics on specified outcomes. Results: We included data from 19 064 men across one RCT and 57 non‐randomised comparative reports. Robotic prostatectomy had a lower risk of major intra‐operative harms such as organ injury [0.4% robotic vs 2.9% laparoscopic], odds ratio ([OR] {95% credible interval [CrI]} 0.16 [0.03 to 0.76]), and a lower rate of surgical margins positive for cancer [17.6% robotic vs 23.6% laparoscopic], OR [95% CrI] 0.69 [0.51 to 0.96]). There was no evidence of a difference in the proportion of men with urinary incontinence at 12 months (OR [95% CrI] 0.55 [0.09 to 2.84]). There were insufficient data on sexual dysfunction. Surgeon learning rates for the procedures did not differ, although data were limited. Conclusions: Men undergoing robotic prostatectomy appear to have reduced surgical morbidity, and a lower risk of a positive surgical margin, which may reduce rates of cancer recurrence and the need for further treatment, but considerable uncertainty surrounds these results. We found no evidence that men undergoing robotic prostatectomy are disadvantaged in terms of early outcomes. We were unable to determine longer‐term relative effectiveness.